Selinexor Enhances NK Cell Activation Against Malignant B Cells via Downregulation of HLA-E - Fisher, Jack G.; Walker, Christopher J.; Doyle, Amber DP.; Johnson, Peter WM.; Forconi, Francesco; Cragg, Mark S.; Landesman, Yosef; Khakoo, Salim. I.; Blunt, Matthew D. (Frontiers in Oncology, 2021)
Selinexor is an FDA approved selective inhibitor of the nuclear export protein exportin-1 (XPO1) and causes specific cancer cell death via nuclear accumulation of tumour suppressor proteins. Design of rational studies for the use of selinexor in combination with other therapeutic agents, such as immunotherapies, requires a fundamental understanding of the effects of selinexor on the immune system. One important emerging area of immunotherapy are natural killer (NK) cell based therapeutics. NK cell function is tightly regulated by a balance of signals derived from multiple activating and inhibitory receptors. Thus in cancer, up-regulation of stress ligands recognised by activating receptors or down-regulation of HLA class I recognised by inhibitory receptors can result in an anti-cancer NK cell response. Changes in XPO1 function therefore have the potential to affect NK cell function through shifting this balance. We therefore sought to investigate how selinexor may affect NK cell function. Selinexor pre-treatment of lymphoma cells significantly increased NK cell mediated cytotoxicity against SU-DHL-4, JeKo-1 and Ramos cells, concurrent with increased CD107a and IFNγ expression on NK cells. In addition, selinexor enhanced ADCC against lymphoma cells coated with the anti-CD20 antibodies rituximab and obinutuzumab. In probing the likely mechanism, we identified that XPO1 inhibition significantly reduced the surface expression of HLA-E on lymphoma cell lines and on primary chronic lymphocytic leukaemia cells. HLA-E binds the inhibitory receptor NKG2A and in accordance with this, selinexor selectively increased activation of NKG2A+ NK cells. Our data reveals that selinexor, in addition to its direct cytotoxic activity, also activates an anti-cancer immune response via disruption of the inhibitory NKG2A:HLA-E axis.